A prognostic nomogram for event-free survival in patients with atrial fibrillation before cardiac resynchronization therapy. (25th November 2020) - Cai, M; Hua, W; Yang, S.W; Zhang, N.X; Hu, Y.R; Gu, M; Niu, H.X; Zhang, S
Abstract: Background: Atrial fibrillation (AF), one of the most common comorbidities with heart failure (HF), is associated with worse prognosis in HF patients receiving cardiac resynchronization therapy (CRT). However, there is still no convenient tool to evaluate and identify patients with high risk of mortality and hospitalization due to heart failure in CRT candidates with AF. Methods: We included 152 consecutive patients with AF for CRT in our hospital from January 2009 to July 2019. Multivariate Cox regression was applied to derive a nomogram, using multiple imputation for missing values and backward stepwise regression for variable selection. Results: Five predictors were incorporated in the nomogram, including N-terminal pro brain natriuretic protein (NTproBNP) >1745pg/mL, history of syncope, previous pulmonary hypertension (PHP), moderate or severe tricuspid regurgitation (TR), thyroid stimulating hormone (TSH) >4mIU/L. Concordance index (0.70, 95% CI 0.62–0.77), corrected concordance index (0.67, 95% CI 0.59–0.74) and calibration curve showed optimal discrimination and calibration of the established nomogram. Significant difference of overall event-free survival was recognized by the nomogram-derived scores in patients with high risk (>50 points), intermediate risk (21–50 points) and low risk (0–20 points) before CRT. Conclusion: Our nomogram may be an applicable tool for early risk stratification among CRT candidates with AF. Funding Acknowledgement: Type of funding source: None